Polymer weathering in Antarctica. (August 2019) - Tocháček, Jiří; Láska, Kamil; Bálková, Radka; Krmíček, Lukáš; Merna, Jan; Tupý, Michael; Kapler, Pavel; Poláček, Petr; Čížková, Klára; Buráň, Zdeněk
Abstract: Antarctica is definitely not a typical locality for polymer testing, and yet, polymers are used there. Antarctic climate is typical with a higher portion of solar ultraviolet (UV) part in the global radiation and extremely low temperatures. Overall effect of Antarctic climatic conditions on polymer environmental degradation was investigated. Weathering experiments were carried out on 0.5 mm isotactic polypropylene homopolymer (h-PP) extruded films - non-UV-stabilized and stabilized with 1000 ppm HALS-1 (low-molecular) and 1000 ppm HALS-2 (oligomeric), respectively. The materials were exposed on James Ross Island in Antarctica for 3 years. A parallel reference series representing weathering in Central Europe (CE) was exposed in Brno, Czech Republic. Climatic data such as incident UV-A, UV-B and global radiation, outdoor air temperatures and total ozone content (TOC) were recorded during the experiment at both exposure sites. Degradation changes in polymer matrix were determined using GPC, FTIR, DSC, TGA, LTHS, SEM techniques and tensile tests. The measurements provided valuable data on h-PP photo-oxidation in Antarctica, on its possible UV stabilization and showed that despite extremes in environmental conditions h-PP degradation rate in Antarctica was still slower compared to CE. Beside UV radiation, higher ambient temperatures accelerating the secondary propagation reactions of alkylperoxy radicals are mainly responsible for the faster photo-degradation in CE. Highlights: Antarctica – a highly specific locality for polymer weathering. Comparison of PP degradation features in Antarctica vs. Central Europe. Up to now, no data on polymer environmental degradation under Antarctic climate was found in scientific literature (WOS).